Role of genomic DNA methylation in detection of cytologic and histologic abnormalities in high risk HPV-infected women - Wiyada Dankai (2019)
© 2019 Dankai et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Cervical cancer is the fourth most common malignancy affecting women worldwide. The development of disease is related to high-risk human papillomavirus (hrHPV) infection. Cytology has been the most recommended triage for primary cervical (pre)cancer screening despite relatively low sensitivity. Recently, genomic DNA methylation has been proposed as an additional marker to increase sensitivity for detecting cervical precancerous lesion. This study aimed to evaluate the performance of methylation status of three tumor suppressor genes (CADM1, FAM19A4, and MAL) and HPV genotyping in detection of cytologic and histologic abnormalities in cervical cancer screening. Two hundred and sixty samples with available frozen cell pellets including 70 randomly selected cases of negative for intraepithelial lesion or malignancy (NILM)&HPV-negative, 70 randomly selected cases of NILM&HPV-positive, and 120 cytologic abnormalities & HPV-positive from a population-based cervical cancer screening program (n = 7,604) were investigated for the DNA methylation pattern of CADM1, FAM19A4, and MAL. Of 120 cytologic abnormalities & HPV-positive cases, there were 115 available histologic results. HPV52 and HPV58 were most commonly found in histologic HSIL+. The methylation levels of CADM1, FAM19A4, and MAL were elevated with the severity of cytologic abnormality which significantly increased by 3.37, 6.65 and 2 folds, respectively, in cytologic HSIL comparing with NILM. A significant increase in methylation levels of these three genes was also observed in histologic HSIL+ compared with negative histology but only CADM1 showed a significant higher methylation level than histologic LSIL. Using the ROC curve analysis, DNA methylation levels of FAM19A4 performed best in differentiating high-grade cytology (ASC-H+ from NILM/ ASC-US/LSIL), followed by CADM1 and MAL. Whilst the CADM1 methylation performed best in distinguishing histologic HSIL+ from negative/LSIL with an area under the ROC curve of 0.684, followed by MAL (0.663) and FAM19A4 (0.642). Interestingly, after combining high DNA methylation levels to HPV16/18 genotypes, rates of histologic HSIL+ detection were substantially increased from 25% to 79.55% for CADM1, 77.27% for FAM19A4, and 72.73% for MAL, respectively. The rate further increased up to 95.45% when at least one of three genes had a high methylation level. This suggests a possible role of genomic DNA methylation, especially CADM1, in detecting histologic HSIL+ lesions in combination with hrHPV testing.